Strength Reduction Factor of Square Reinforced Concrete Column Using Monte Carlo Simulation - Wahyuniarsih Sutrisno; Bambang Piscesa; Mudji Irmawan (Journal of Civil Engineering, 2020)
This paper investigates the strength reduction factor (f) of reinforced concrete (RC) columns using Monte-Carlo simulation (MCS). The main objective of this paper is to evaluate the strength reduction factor of the RC using the authors' developed code. This code is important for further research to check other important effects when high-strength materials are used. The investigated RC column concrete compressive strengths (fc) are 40 and 60 MPa while the rebar strengths (fy) are set to 320, 400, and 500 MPa. Fiber-based cross-sectional analysis is used to compute the axial-moment interaction capacity of the RC column. The concrete compressive block is used to model the concrete contribution and the bilinear stress-strain model is adopted for the rebar. These simplifications can reduce the difficulties when solving the equilibrium of the forces in the sectional analysis. The parameters used in the sensitivity analysis of the strength reduction factor (f) are the concrete compressive strength (fc), the rebar yield strength (fy), the longitudinal rebar ratio (r), and the column size (b,h). The effect of the coefficient of variations for each material on the resistance variation coefficient of the RC is also investigated. From the analysis, it can be concluded that when the RC column falls in the tension-controlled region, the obtained strength reduction factor is 0.93 which is slightly higher than the value of f in ACI 318-19. On the other hand, when the RC column falls in the compression-controlled region, the obtained strength reduction factor is 0.6 which is lower than the value of f in ACI 318-19 which is 0.65.